Trends and events through seven centuries: the history of a wetland landscape in the Czech Republic - Szabó, Péter; Gálová, Andrea; Jamrichová, Eva; Šumberová, Kateřina; Šipoš, Jan; Hédl, Radim (Regional environmental change, 2017)
Environmental change can be viewed as the combined result of long-term processes and singular events. While long-term trends appear to be readily available for observation (in the form of temporal comparisons or space-for-time substitution), it is more difficult to gain information on singular events in the past, although these can be equally significant in shaping ecosystems. We examined the past 700 years in the history of a lowland wetland landscape in the Czech Republic with the help of palaeoecological, ecological, landscape archaeological, and archival data. Macrofossil and pollen data were compared to known drainage works in the area and historical climatological data. Trends and events in habitat conditions were assessed using species indicator values. Results showed that ecological succession was the general process in the study area, detected as a trend towards eutrophication, desiccation and vegetation closure. Short-term events influenced development at the sites mainly from the second half of the 19th century. This is consistent with drainage history, although bias related to sample frequency cannot be excluded. On the whole, long-term trends and discrete events were complementary on different scales. We conclude that humans facilitated and accelerated background processes, which can be most likely associated with the succession of open wetlands towards terrestrial ecosystems.
Keywords: pollen; human impact; macrofossils; vegetation development; species indicator values; drainage channels